Synthesis of α‐D‐Ribose 1‐Phosphate and 2‐Deoxy‐α‐D‐Ribose 1‐Phosphate Via Enzymatic Phosphorolysis of 7‐Methylguanosine and 7‐Methyldeoxyguanosine. Issue 1 (20th January 2022) - Varizhuk, Irina V.; Oslovsky, Vladimir E.; Solyev, Pavel N.; Drenichev, Mikhail S.; Mikhailov, Sergey N.
Abstract: A simple and efficient method for the preparation of α‐D ‐ribose 1‐phosphate and 2‐deoxy‐α‐D ‐ribose 1‐phosphate, key intermediates in nucleoside metabolism and important starting compounds for the enzymatic synthesis of various modified nucleosides, has been proposed. It consists in near‐irreversible enzymatic phosphorolysis of readily prepared hydroiodide salts of 7‐methylguanosine and 7‐methyl‐2′‐deoxyguanosine, respectively, in the presence of purine nucleoside phosphorylase. α‐D ‐Ribose 1‐phosphate and 2‐deoxy‐α‐D ‐ribose 1‐phosphate are obtained in near quantitative yields (by HPLC analysis) and 74%‐94% yields after their isolation and purification. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of α‐D ‐ribose 1‐phosphate barium salt (4a ) Alternate Protocol 1 : Preparation of 2‐deoxy‐α‐D ‐ribose 1‐phosphate barium salt (4b ) Basic Protocol 2 : Preparation of α‐D ‐ribose 1‐phosphate bis(cyclohexylammonium) salt (5a ) Alternate Protocol 2 : Preparation of 2‐deoxy‐α‐D ‐ribose 1‐phosphate bis(cyclohexylammonium) salt (5b )